Pemberitaan Masalah Rumah Tangga Selebritis sebagai Media spectacle (Guy Debord) - Mutia Rahmi Pratiwi (Jurnal Komunikasi, 2014)
Television has become an integral part of the community. Television presents a variety of diverse programs that include educational information, news and even entertainment gossip into the infotainment program. Among the various programs, infotainment now to be excellent for the television audience because many issues debated households are packed into the sensational news, ranging from gonogini property issues, differences in belief, a large family conflict, inequality of income, until the emergence of a third part which further adds chaotic household. Various household problems Infotainment packaging style will be the center of attention of the audience infotainment to continue watching the story of the conflict, like watching endless soap opera. This paper discusses the issues of households reporting celebrities as a media spectacle.